The Release of Curcumin from β-TCP/SiO₂/Curcumin Composites in a Ringer’s Lactate Solution - Tri Windarti; Ngadiwiyana Ngadiwiyana; Fadila Fibriani (Jurnal Kimia Sains dan Aplikasi, 2026)
Osteoporosis is characterized by bone deterioration caused by high levels of reactive oxygen species (ROS), which inhibit osteoblast activity and lead to a decrease in bone density. Adding curcumin, a natural antioxidant, to calcium phosphate cement (CPC) enhances its function beyond simply increasing bone density. In this study, CPC was prepared from a β-tricalcium phosphate (β-TCP, β-Ca3(PO4)2) composite with curcumin. To enhance the interaction between β- TCP and curcumin, silicon dioxide (SiO2) was added. β-TCP was synthesized by the sol-gel method, with SiO2 content ranging from 1.6 to 8.3%. CPC preparation was carried out using a 2.5% Na2HPO4 solution. The release of curcumin in a Ringer’s lactate solution was studied in relation to the role of SiO2. The UV-Vis spectral intensity of the remaining Ringer’s lactate solution after soaking decreased as the SiO2 content increased. Results from a five-day soaking period showed that β-TCP did not transform into hydroxyapatite, but rather experienced a decrease in crystallinity and average crystal size from 96.175% to 25.524% and from 58.335 nm to 39.474 nm, respectively. Therefore, it can be predicted that CPC can maintain the presence of curcumin in a physiological environment.